The Influence of Information Technology Utilization and Use on the Quality of Financial Reports - Hadrah Hadrah; Muhammad Ahsan Abdul Latief (INCOME: Innovation of Economics and Management, 2024)
The aim of this research is to determine the effect of the use of information technology and information technology users on the quality of financial reports. The population in this study were employees of PAM Tirta Latimojong, Luwu Regency. Meanwhile, the research sample is the quality of financial reports. The population in this study were all employees of Perumda Latimojong and the sample in this study was 76 people. In this research, the associative type was used with a quantitative approach with testing using multiple linear regression. The results of this research show that the variables Utilization of information technology and users of information technology have a significant effect on the quality of financial reports.